Land Cover Dynamics and Environmental Implications in Türkiye’s Riparian Zones: A Comprehensive Seven-Year Study - Akturk, Emre; Guney, Kerim; Aydin, Mirac; Yildiz, Faruk; Kaya, Ozkan (MDPI AG, 2024)
This study examines the Riparian Buffer Zones (RBZs) in Türkiye, analyzing land cover changes from 2017 to 2023 to assess their effectiveness in ecological conservation and water resource management. The research employs Esri-Sentinel land cover data, Shuttle Radar Topography Mission digital elevation models, and RiverATLAS data to identify and delineate RBZs, classify land cover types, and evaluate trends and changes over seven years. The findings indicate that 44.8% of RBZs are covered by ‘Rangelands’, 32.2% by ‘Crops’, and 16.1% by ‘Trees’ classes. The study notes a considerable increase in built areas and agricultural fields, which may indicate ongoing urban expansion and its potential impact on the effectiveness of RBZs. Despite regulatory efforts, the substantial presence of agriculture within RBZs indicates a need for more robust environmental protection policies. The results indicate a pressing need for a policy reassessment to enhance forest cover within RBZs and reduce agricultural encroachment. This would improve water quality and facilitate the achievement of sustainability goals numbered 2, 3, 6, 11, 14 and 15. The findings thus call for a strategic enhancement of RBZ management to better protect water resources against the adverse effects of agricultural and urban activities.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water